Efecto Del Incremento De Intensidad Y Frecuencia Semanal Sobre La Condición Física En Personas Mayores Activas Que Proporcionan Los Programas: Ejercicio Funcional Con Bandas Elásticas Vs Lúdico- Recreativo - Franco, Christian Hernán Ponce; Bravo, Hernán Leopoldo Ponce; Cayo, Henry Rodolfo Gutiérrez; Brito, Karolina Janeth Cando; Machado, Ramón Fernando Bayas (European Scientific Journal, ESJ, 2017)
This study examines the impact of a program of functional exercise with elastic resistance band (centered on joint multi-resistance elastic band; experimental group, EG) versus an entertainment content (recreational exercise program compared to a recreational exercise program; control group, CG). It also examines the physical fitness in older active people who are over 60 years. Fifty-four volunteers who are residents of the community have an age range (70.57 ± 5.46 years). Before and after the intervention, physical fitness was determined through the Senior Fitness Test (strength, flexibility, aerobic endurance, and agility-dynamic balance) and the Manual Dynamometry Test. In the comparison INTER groups, the EG in flexibility improves p < 0.05 and in dynamic agility-balance p < 0.01. INTRA groups, EG and CG in leg and arm strength, presented improvements p < 0.001 and in manual isometry p < 0.05. Based on the flexibility of legs and arms, the EG presents improvements p < 0.05. Also, the CG only in right arm flexibility presents improvement p < 0.05. In agility-dynamic equilibrium, only the EG presents improvement p < 0.01. In expected aerobic performance, only the CG presented improvement p < 0.05. Strength improvement and increased manual grip maintain functional autonomy in both groups. Coupled with the improved agility-dynamic balance and flexibility of the EG, it gives the adult more independence which reduces the risk of falls in this population. In our findings, the EG significantly improved all fitness variables to a greater extent than CG. We recommend an increase in the intensity and frequency of physical activity programs and the inclusion of functional exercises with elastic bands aimed at this population.